Negotiating better teamwork. general instruction / Part one, - Collins, William, active 2024, (SAGE Business cases., 2024)
Lee, a member of an MBA program team facing interpersonal challenges, takes a contemplative walk to prepare for a tough conversation with an underperforming team member. The team, formed just three months ago, struggles with internal conflicts, and Lee believes addressing this issue early is essential for future success. He embraces this opportunity to develop leadership skills by providing clear feedback, active listening, seeking constructive solutions, focusing on behavior rather than personality, and managing emotions without judgment.